Estimation of some biochemical markers in diabetic patients with renal impairment (Open Herald: Periodical of Methodical Research, 2025)
Diabetes mellitus (DM) is a chronic disorder involving multiorgan dysfunction on the long term, uncontrolled DM could have many complications on top renal impairment, peripheral neuropathy and retinopathies. The study involved 120 DM cases of which 60 with renal impairment and 60 without renal impairment who attended Diabetic clinic at private clinics during June to August 2024 in addition to 60 control healthy subjects. All patients and control subjects were assessed for basic renal function and glomerular filtration rate (GFR) as well as serum Potassium and HbA1c in addition to Early region 2 binding factor (E2F1), Amylin and Glucagon-like peptide 1 (GLP-1) via ELISA assay. Our data revealed that mean age and BMI of DM cases were 58.18 years and 28.03 respectively. Blood urea, HbA1c and GFR were significantly higher in BM with renal impairment compared to control P